Ecological Effects of Daily Antiseptic Treatment on Microbial Composition of Saliva-Grown Microcosm Biofilms and Selection of Resistant Phenotypes - Mao, Xiaojun; Hiergeist, Andreas; Auer, David L.; Scholz, Konstantin J.; Muehler, Denise; Hiller, Karl-Anton; Maisch, Tim; Buchalla, Wolfgang; Hellwig, Elmar; Gessner, André; Al-Ahmad, Ali; Cieplik, Fabian (Frontiers in Microbiology, 2022)
Antiseptics are widely used in dental practice and included in numerous over-the-counter oral care products. However, the effects of routine antiseptic use on microbial composition of oral biofilms and on emergence of resistant phenotypes remain unclear. Microcosm biofilms were inoculated from saliva samples of four donors and cultured in the Amsterdam Active Attachment biofilm model for three days. Then, they were treated twice daily with chlorhexidine digluconate (CHX) or cetylpyridinium chloride (CPC) for a period of seven days. Ecological changes upon these multiple antiseptic treatments were evaluated by semiconductor-based sequencing of bacterial 16S rRNA genes and identification of amplicon sequence variants (ASVs). Furthermore, culture-based approaches were used for colony forming units (CFU) assay, identification of antiseptic-resistant phenotypes using an agar dilution method and evaluation of their antibiotic susceptibilities. Both CHX and CPC showed only slight effects on CFU and could not inhibit biofilm growth despite the twice daily treatment for seven days. Both antiseptics showed significant ecological effects on the microbial compositions of the surviving microbiota, whereby CHX led to enrichment of rather caries-associated saccharolytic taxa and CPC led to enrichment of rather gingivitis-associated proteolytic taxa. Antiseptic-resistant phenotypes were isolated on antiseptic-containing agar plates, which also exhibited phenotypic resistance to various antibiotics. Our results highlight the need for further research into potential detrimental effects of antiseptics on the microbial composition of oral biofilms and on spread of antimicrobial resistance in the context of their frequent use in oral health care.